Crisis and economic policy: the Spanish experience under the Spanish Socialist Workers Party - Estuve, Fernando (1988)
​In recent years there has been a growing international attention to the economic model put forward by the Spanish socialist government to face economic crisis, making substantial use of social agreements. This article artalyzes the economic policy of the socialist government and its theoretical foundations, attempting to judge them on the basis of efficiency and equity criteria.